Readiness of State Junior High School 18 Tanjung Jabung Timur in Implementing Digital-Based Promotion - Hajrawati; Mohamad Muspawi; Robi Hendra (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to describe the readiness of SMP Negeri 18 Tanjung Jabung Timur in implementing digital-based promotions in the era of information technology transformation. The background of this study departs from the condition of the school which experienced a significant decline in the number of students and the low utilization of digital media in school promotional activities. This study uses qualitative and quantitative approaches with a descriptive research type, through data collection techniques in the form of observation, interviews, documentation, and distribution of questionnaires to the principal, vice principal, school operators, and social media administrators. Data analysis was carried out through the processes of data reduction, data presentation, triangulation, and drawing conclusions. The results of the study indicate that SMP Negeri 18 Tanjung Jabung Timur is quite ready to implement digital-based promotions, but not yet optimal. Of the four main indicators, technological infrastructure readiness is quite adequate, with the availability of computers, an internet network, and a school social media platform, although not yet fully utilized. Regarding the human resources indicator, the digital competence of teachers and education personnel is still limited, requiring ongoing training and mentoring. The policy and management support indicator indicates the school's commitment, but it is not yet supported by structured strategic planning. Meanwhile, the procedure indicator for implementing digital promotions has not been implemented consistently due to the lack of operational guidelines and periodic evaluations. Based on these findings, schools need to improve the digital competency of their human resources, refine work program-based digital promotion planning, strengthen management policies, and optimize the use of digital platforms to ensure effective and sustainable promotional strategies. This research is expected to serve as a reference for other schools in developing digital promotion strategies as part of increasing educational institution competitiveness in the digital era.